The Artificial intelligence in Power Systems (International Journal of Innovative Research in Computer Science & Technology, 2022)
Electricity is required in every country  and state, so if the electricity is required, then a consistent  and good as well as dependable electricity supply is  required. ML is becoming growing and vast in the every  fields of the work, such as electrical powers system,  electronic parts, work software’s and tools, and  construction. Artificial intelligence (AI) is becoming  increasingly important in everyday life, including home  and business automation. The amount of research being  done on the power system is growing years by years, and  today AI is being used to make power systems smarter.  Power systems are based on geography, weather, or any  specific area. Other factors that the power system is reliant  on include the introduction of new technologies, the  upgrading and modification of technology and equipment,  energy transmission, and distribution. AI stands for  artificial intelligence, which is a sophisticated approach for  assessing and solving any problem. As a result, it may be  used to address a variety of issues that arise in power  systems, such as control, planning, scheduling, and  prediction. The scope of AI for power systems as well as  the use of AI in handling intricate electrical connections  were discussed in this article.
Keywords: AI; Circuit; Electrical; Power; System